CONFRONTING INTERSECTIONAL DISCRIMINATION IN THE INTER-AMERICAN HUMAN RIGHTS SYSTEM: CONTRIBUTIONS OF IACTHR TO THE CONSTRUCTION OF ANTI-DISCRIMINATION LAW - DA SILVA, Waldimeiry Corrêa; Garbellini Filho, Luiz Henrique [UNESP] (My University, 2024)
Objective: To analyze the approach of the Inter-American Court of Human Rights (IACtHR) regarding intersectional discrimination based on three decisions that contain provisions on non-discrimination and the guarantee of equality. Methodology: This is critical, descriptive, and explanatory research through qualitative analysis of the content of the judicial decisions of the IACHR supported by the analytical framework of intersectional perspectives. A dialectical approach is adopted to problematize the relationship between the intersectional paradigms consolidated in the literature and their application by judges in the primary sources of this study. Results: On one hand, the application of the intersectional paradigm has been refined to analyze the intersection of prohibited causes of discrimination more complexly, as well as to better determine the scope of state responsibilities regarding human rights violations. On the other hand, they identify both the prevalence of unitary and multiple paradigms on discrimination in multilateral human rights treaties (MHRTs) of the Inter-American Human Rights System (IAHRS) and the restriction of the development of the intersectional approach in the decisions of the IACtHR. Contributions: The research makes it possible to visualize the contributions and limitations of addressing intersectional discrimination by the IACtHR. Thus, it reveals the problems that hinder the coverage of the complexity of the discriminations suffered by rights holders and, thereby, contributes more effectively to the construction of anti-discriminatory law not only within the framework of the Organization of American States (OAS) but also for the international community.
LA CONFRONTACIÓN A LA DISCRIMINACIÓN INTERSECCIONAL EN EL SISTEMA INTERAMERICANO DE DERECHOS HUMANOS: APORTACIONES DE LA CORTE IDH A LA CONSTRUCCIÓN DEL DERECHO ANTIDISCRIMINATORIO
Keywords: anti-discriminatory law; Inter-American Court of Human Rights; Inter-American Human Rights System; intersectional discrimination